Upgrading logic programming in hopfield network - Saratha Sathasivam, (Penerbit Universiti Kebangsaan Malaysia, 2010)
The convergence property for doing logic programming in Hopfield network can be accelerated by using new relaxation method. This paper shows that the performance of the Hopfield network can be improved by using a relaxation rate to control the energy relaxation process. The capacity and performance of these networks is tested by using computer simulations. It was proven by computer simulations that the new approach provides good solutions.